New anti terror law should have real teeth to combat militancy, say analysts - Borneo Post, (Kuching) (BorneoPost Online, 2015)
KUALA LUMPUR: The so called IS militant group, which is using social media as a tool to recruit members, is being seen by many countries, including the superpowers, as a great security threat which can destablise the world.